Intelligent Energy Saving Switching System - S. Sidek;; R. Muhammad Afiq;; M.A. Muhammad Hamidi (Universiti Sains Islam Malaysia, 2024)
A lot of energy is wasted when lights, air-conditioning unit and other electrical devices are still running without anybody inside the room. This situation frequently occurred at small offices or classrooms when the last person leaving the room forgot to switch off the lights and air-conditioning unit. A system which is able to detect the number of people entering and leaving a room is developed to overcome this problem. The system has sensors located inside, outside and at the door frame of the room entrance to detect the person movement leaving or entering the room. When a person enters the room, the movement of the person is detected and the counter of the controller will start the incremental counting to record the number of person entering the room. Electrical supply of the room will be automatically switched on at the moment the first person entering the room. When the people inside the room start leaving the room, the counter will count downwards. The electrical supply will be turned off automatically when the counter reaches .